Apoiando a criação de extensões da linguagem KAOS (Knowledge Acquisition in Automated Specification) - Monte, Leandro da Silva (2024)
Goal-Oriented Requirements Engineering (GORE) supports the development team in identifying the requirements that the system must fulfil. Commonly applied during the initial stages of requirements gathering, it focuses on identifying the system’s goals, presenting their decom- position as a means of offering alternatives that can satisfy them. Knowledge Acquisition in Automated Specification (KAOS) is a GORE approach that consists of a method, a software environment, and a modelling language. Modelling languages can be adaptable to various types of domains/application areas in which the software will be developed. In this way, extensions are proposed to adapt the modelling to the desired scenarios. These adaptations are referred to as extensions. KAOS has been extended to different areas such as security, adaptive systems, aspects, among others. The proposition of new KAOS extensions has been growing and is expected to continue in the coming years, as it is necessary to adapt the languages to the many different types of existing contexts or those that emerge with the constant evolution in software development. Creating an extension is a complex task with a set of inherent challenges, such as maintaining consistency between the extension being created and the existing ones. Given these facts, we recognise the need to support the creation of KAOS language extensions. This study aims to support the systematic creation of new KAOS extensions. The first step involves updating a Systematic Literature Review (SLR) on the existing KAOS extensions. Additionally, a process to support the creation of new KAOS extensions was proposed. The proposed process was used to create a KAOS extension to represent accessibility concepts, which proved valid for this purpose. Finally, the PRAOS process was evaluated by KAOS extension specialists through a qualitative study.